2014
DOI: 10.1007/s00418-014-1289-8
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular characterization of a novel primary osteoblast culture from the vertebrate model organism Xenopus tropicalis

Abstract: Osteogenesis is the fundamental process by which bones are formed, maintained and regenerated. The osteoblasts deposit the bone mineralized matrix by secreting large amounts of extracellular proteins and by allowing the biochemical conditions for the nucleation of hydroxyapatite crystals. Normal bone formation requires a tight control of osteoblastic activity, and therefore, osteoblasts represent a major focus of interest in biomedical research. Several crucial features of osteogenesis can be readily recapitul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Recent studies have revealed that osteoblasts of earlier-diverged clades, such as bony fishes and amphibians, express molecular markers normally associated with cartilage of later-diverged clades, such as mammals and birds [25][26][27][28]. A big surprise came when extremely high levels of col10a1 expression (again, THE definitive marker of mature chondrocytes in chick and mouse) were demonstrated in osteoblasts of both zebrafish and gar [25].…”
Section: Osteoblasts Suppressed Chondrocyte Genes During Evolutionmentioning
confidence: 99%
“…Recent studies have revealed that osteoblasts of earlier-diverged clades, such as bony fishes and amphibians, express molecular markers normally associated with cartilage of later-diverged clades, such as mammals and birds [25][26][27][28]. A big surprise came when extremely high levels of col10a1 expression (again, THE definitive marker of mature chondrocytes in chick and mouse) were demonstrated in osteoblasts of both zebrafish and gar [25].…”
Section: Osteoblasts Suppressed Chondrocyte Genes During Evolutionmentioning
confidence: 99%
“…To characterize in greater details such perpendicular processes, we took advantage of the fact that the developing X. tropicalis calvaria contains two mirror‐image osteocyte fields derived from osteoblasts lying onto the bone surfaces facing the brain or the skin (see Fig. A; Espinoza et al., ; Bertin et al., ). Because these two fields grow in opposite directions, the middle region of the calvaria is mostly devoid of osteocytes and cell processes (dotted line in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Nieuwkoop and Faber developmental table was applied to X. tropicalis larvae and used to select fully mineralized calvaria at stage NF60 (Nieuwkoop and Faber, ; Espinoza et al., ). Xenopus tropicalis tadpoles were anaesthetized with tricaine, killed by decapitation (Close et al., ; Rhee et al., ), and the dissected calvaria were stripped from all superficial cells by a series of protease treatments, as previously described (Bertin et al., ). Calvaria were washed in Hank's Balanced Salt Solution 0.6× (Hyclone, Logan, UT), fixed in 4% PFA overnight at 4°C, and gently washed four times in PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…X. tropicalis and the Marsabit clawed frog X. borealis are widely used in many laboratories for genetic and developmental studies (114)(115)(116)(117)(118)(119). Although X. tropicalis is more widely used, X. borealis is more closely related to X. laevis (120).…”
Section: Xenopus Borealis As An Alternative Source Of Oocytes For Biomentioning
confidence: 99%